MODEL KOOPERATIF TEAMS GAMES TOURNAMENT DALAM PEMAHAMAN KONSEP MATEMATIS: SYSTEMATIC LITERATURE REVIEW - Juwita Kirana Wulandari; Syamsuri Syamsuri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Mathematical conceptual understanding is a fundamental competency in mathematics education; however, the effectiveness of various instructional models in fostering this ability continues to yield mixed findings. At the same time, studies specifically mapping the relationship between the Teams Games Tournament (TGT) model and mathematical conceptual understanding remain limited. This situation prompted a systematic review to provide a more comprehensive picture of research trends, implementation characteristics, and the contribution of TGT to strengthening students’ conceptual understanding. The review employed a Systematic Literature Review approach by examining articles indexed in Google Scholar published between 2022 and 2025 using keywords related to TGT and mathematical conceptual understanding. The selection process followed the PRISMA framework and resulted in 24 articles that met the inclusion criteria, which were subsequently analyzed through content analysis and thematic synthesis. The findings indicate that TGT is consistently associated with improved conceptual understanding through collaborative learning activities, academic games, tournaments, active student participation, and the use of supporting instructional media. Its effectiveness tends to be greater when conceptual indicators are clearly defined and learning activities are aligned with the characteristics of the subject matter. Research publications were most prevalent in 2023, predominantly conducted at the elementary school level and frequently focused on number-related topics. These findings suggest that TGT is a highly relevant instructional strategy for promoting interactive and collaborative mathematics learning while highlighting opportunities for further investigation in more abstract mathematical topics and higher educational levels. ABSTRAK Pemahaman konsep matematis merupakan salah satu kompetensi penting dalam pembelajaran matematika, namun efektivitas berbagai model pembelajaran dalam mendukung kemampuan tersebut masih menunjukkan temuan yang beragam. Di sisi lain, kajian yang secara khusus memetakan hubungan antara model Teams Games Tournament (TGT) dan pemahaman konsep matematis masih terbatas. Kondisi ini mendorong dilakukannya kajian sistematis untuk memperoleh gambaran yang lebih utuh mengenai kecenderungan penelitian, karakteristik penerapan, serta kontribusi TGT terhadap penguatan pemahaman konsep matematis. Kajian dilakukan melalui pendekatan Systematic Literature Review dengan menelusuri artikel yang terindeks Google Scholar pada periode 2022–2025 menggunakan kata kunci yang berkaitan dengan TGT dan pemahaman konsep matematis. Proses seleksi mengikuti alur PRISMA dan menghasilkan 24 artikel yang memenuhi kriteria inklusi, kemudian dianalisis menggunakan content analysis dan sintesis tematik. Pola temuan menunjukkan bahwa TGT secara konsisten dikaitkan dengan peningkatan kualitas pemahaman konsep melalui aktivitas kolaboratif, permainan akademik, turnamen, partisipasi aktif siswa, serta pemanfaatan media pendukung pembelajaran. Efektivitas tersebut cenderung lebih optimal ketika indikator konsep dirancang secara jelas dan aktivitas belajar disesuaikan dengan karakteristik materi. Publikasi penelitian paling banyak ditemukan pada tahun 2023, didominasi oleh jenjang Sekolah Dasar, serta banyak diterapkan pada materi bilangan. Temuan ini memperlihatkan bahwa TGT memiliki relevansi yang kuat sebagai strategi pembelajaran matematika yang interaktif dan kolaboratif, sekaligus membuka peluang pengembangan kajian pada materi yang lebih abstrak dan jenjang pendidikan yang lebih tinggi.